Computational case study on tangent hyperbolic hybrid nanofluid flow: single phase thermal investigation - Jamshed, Wasim; Nisar, Kottakkaran Sooppy; Mohamed Isa, Siti Suzilliana Putri; Batool, Sawera; Abdel Aty, Abdel Haleem; Zakarya, Mohammed (Elsevier, 2021)
Heat transmission is inevitable in industrial and manufacturing processes. The hybrid nanofluid with its advanced thermal exponent due to the two-part nanoparticle which helps to boost the thermal transfer capacity of standard nanofluids to achieve it. The flow and thermal transference properties of hybrid nanofluid of such kind via a slippery surface has investigated in this study. The pore mediums, heat source, viscous dissipation, thermal conducting variants, and thermal radiative impacts were explored. The controlled equations are solved using the finite difference numerical methodology. The hybrid Tangent hyperbolic nanofluid, which is made up of viscous non-Newtonian fluid EG (ethylene glycol) and two types of nano-solid particles of copper (Cu) and titanium dioxide (TiO2) has been studied. It's worth noting that, when compared to the conventional nanofluid (Cu-EG), the heat transfer level of TiO2–Cu/EG hybrid combo has been continuously increased. The thermal efficiency of TiO2–Cu/EG over Cu-EG is realized with a least of 1.4% and supreme of 3.3%. By integration of nanoparticles ratio, the entropy system is enlarged due to fractional size, radiative variant, thermal conductance and the Weissenberg number.